Associations between Oxidant/Antioxidant Status and Circulating Adipokines in Non-Obese Children with Prader-Willi Syndrome - Joanna Gajewska; Jadwiga Ambroszkiewicz; Katarzyna Szamotulska; Grażyna Rowicka; Małgorzata Strucińska; Witold Klemarczyk; Magdalena Chełchowska (MDPI AG, 2023)
Oxidative stress is implicated in the pathophysiology of Prader-Willi syndrome (PWS), but there are no data on these disorders in non-obese children with PWS. Therefore, the presented study examined total oxidant capacity (TOC), total antioxidant capacity (TAC), the oxidative stress index (OSI), and adipokine levels in 22 non-obese children with PWS during dietary intervention and growth hormone treatment compared with 25 non-obese healthy children. Serum concentrations of TOC, TAC, nesfatin-1, leptin, hepcidin, ferroportin, and ferritin were determined using immunoenzymatic methods. We found that TOC concentrations were higher by 50% (p = 0.006) in patients with PWS than in healthy children, but no significant differences in TAC concentrations were observed between these groups. The OSI was higher in children with PWS than in the controls (p = 0.002). We found positive associations between TOC values and the percentage of the Estimated Energy Requirement, body mass index (BMI) Z-score, percentage of fat mass, and leptin, nesfatin-1, and hepcidin concentrations in patients with PWS. A positive association was also found between the OSI and nesfatin-1 levels. These observations suggest that higher daily energy intake and weight gain may be accompanied by an increasing prooxidant state in these patients. Adipokines such as leptin, nesfatin-1, or hepcidin may also play a role in the prooxidant state in non-obese children with PWS.